PERLINDUNGAN KONSUMEN DALAM KLAIM ASURANSI BARANG PADA PEMBIAYAAN KENDARAAN BERMOTOR DIKAITKAN DENGAN PERJANJIAN MODEL BAKU - priyono, yose (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
Standard model agreement in business is often used like that of consumer finance transaction, in its scheme which is easy, practical, and not time consuming. However, on a case of insurance provision claim, this kind of agreement could not provide any protection to the consumer, since the provisions in the agreement were seattled unilaterally by the auto financing company. By using normative juridical and sociological approach, this study found that a standard model agreement does not provide protection to consumers as debtors for their claim of good damage. This is contrary to the provisions of standard clauses set out in article 18of consumer protection legislation which consequently make that agreement void. The concept of consumer protection in auto financing insurance must provide clarity and time for a consumer to comprehend the agreement clearly to avoid any financial lost during the practice of the agreement.